(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Premessa - 2. La fase antepraeparatoria (1959-1960) - 3. La fase praeparatoria (1960-1962) - 3.1. La prima sessione plenaria (12 e 15 novembre 1960) - 3.2. La Relatio De musica sacra presentata alla seconda sessione plenaria (12-22 aprile 1961) - 3.3. Il dibattito sulla Relatio De Musica sacra nella seconda sessione plenaria - 3.4. La Relatio De Musica sacra dopo la seconda sessione plenaria - 4. La redazione dello Schema presentato al Concilio - 5. Il dibattito conciliare sulla Liturgia (1962-1963) e l’approvazione della Costituzione Conciliare Sacrosanctum Concilium. Music and theology in Sacrosanctum Concilium: the munus ministeriale of music in the liturgy ABSTRACT: The focus of this article is showing the relationship between music and theology in the Constitution on The Sacred Liturgy (Sacrosantum Concilium). Initially, the article examines the altiora principia of SC in Chapter I which represents the context in which to interpret Chapter VI on the sacred music. Then, from the study of their redactional process, there’s a detailed review of some of the numbers from the same chapter on the sacred music, in order to show how some expressions were elaborated to define the connection between music and theology, especially munus ministeriale.